Mental Health in Sport (MHS): Improving the Early Intervention Knowledge and Confidence of Elite Sport Staff - Sebbens, Joshua; Hassmén, Peter; Crisp, Dimity; Wensley, Kate (Frontiers in Psychology, 2016)
Mental illnesses are as prevalent among elite athletes as in the general population. Despite this, there is little research examining how to enhance mental health literacy or helping behaviors in elite sport environments. A 4-hour Mental Health in Sport (MHS) workshop was therefore developed and its effects on mental health literacy and confidence studied in 166 coaches and support staff working with elite athletes and teams in Australia. Results indicated that participants increased their knowledge of the signs and symptoms of common mental illnesses and were more confident in helping someone who may be experiencing a mental health problem. We conclude that even a very brief intervention can be effective in improving the mental health literacy and confidence of key persons in elite sport environments, and may promote early intervention and timely referral of elite athletes with mental health concerns to appropriate professionals.